Penal protection for children subject to moral neglect - Amokrane, Abderrezak (Journal of Human Sciences, 2023)
Family is the natural environment for children’s growth as it guarantees them the best moral and physical development in view of circumstances away from various forms of family neglect. The Algerian legislator has endeavoured to strengthen its role and devote indispensable protection to children subject to family neglect (particularly moral neglect) throughout the Constitution enacted in 2020 (Article 71 thereof), as well as through the provisions of both the Family Law No.05-02 and the Child Protection Law No.15-12, in addition to those laid down in the Penal Law No. 66-156, as amended and supplemented by the Law 21-14 issued on 2021,. Nonetheless, even with the protection provided by all such provisions for the child together with securing his family environment, these exerted efforts remain insufficient in view of the growth of crime within the family milieu, mainly the crime of moral neglect of children, the fact of which has shown to be generally due to the globalization and the negative repercussions of modern technology on lifestyles within the family, alongside the subsequent changes witnessed in the principles of family formation and the purpose of its existence.